Milletlerarasi sempozyum Islam dusuncesinin 20, asirda yemiden yapdanmasi (Istanbul: AKM Istanbul Organization [production company], 1992)
Internatinal symposium the constraction of Islami thought in the 20th century and Bediuzzaman Said Nursi